Comparison of functional outcome after early and delayed anterior cruciate ligament reconstruction: A systematic review - I Putu Dharma Kresna; Kukuh Dwiputra Hernugrahanto; Rr. Indrayuni Lukitra Wardhani; Dwikora Novembri Utomo (Universitas Muhammadiyah Surabaya, 2022)
This study aims to find the optimal timing for Anterior Cruciate Ligament (ACL) reconstruction by comparing the outcome of early versus delayed ACL reconstruction, meniscus, and chondral damage. A systematic literature search was performed from February to March 2021 from 4 databases. Inclusion criteria were English language Randomized Control Trial (RCT) and observational studies published in 2000-2020, 20-50 years old patients with an isolated ACL tear with/without meniscal injury underwent ACL reconstruction. Early ACL reconstruction was estimated at less than six weeks post-injury, and delayed ACL reconstruction was estimated at more than six weeks. Tegner and Lysholm were the functional outcomes to compare early and delayed ACL reconstruction with a meniscus tear and chondral damage. The search yielded 3094 studies. After removing duplicates, titles and abstracts were screened, leaving 154 potential studies. The studies were selected, and eight studies were eligible. No statistically significant difference between early and delayed ACL reconstruction in Lysholm and Tegner score (p>0,05) was found. Both scores were similar regarding whether the patient performs early/delayed ACL reconstruction. Therefore, early ACL reconstruction could be an optimal timing for the patient who will undergo ACL reconstruction.